Mangrove Health Monitoring System - Ruzaima, Khairul Azroy (Universiti Teknologi PETRONAS, 2018)
Mangroves are usually can be found in tropical across coastlines, river and creek. Mangroves live in the soil which almost always salty and waterlogged. Malaysia also has mangrove forests which are known as the Matang Mangrove Forest. It is the largest single mangrove forest and very valuable nature in peninsular Malaysia. Monitoring of mangrove forest is required more efficient tools like remote sensing technique. This is very important because to make sure that mangrove forest will be safe and secure. Remote sensing technique is one the most reliable alternative compares to ground-survey methods that provide very useful information about the mangrove condition that is timely especially in mangrove area which is very difficult to access. This is very vital due to extinction of mangrove tree.